2016
DOI: 10.1039/c5ce02154e
|View full text |Cite
|
Sign up to set email alerts
|

Extending the halogen-bonded supramolecular synthon concept to 1,3,4-oxadiazole derivatives

Abstract: A series of five crystal structures of 1 : 1 halogen-bonded complexes were obtained from 4-[5-(4-alkoxyphenyl)-1,3,4-oxadiazole-2-yl]pyridine and 1,3,5-trifluorotriiodobenzene. Electronic structure calculations show that the N (oxadiazole) ⋯I interaction in the new synthon is as strong as the classic N (pyridine) ⋯I interaction. Oxygen to sulfur atom subsitution on the oxadiazole ring results in a different supramolecular packing where the N (pyridine) ⋯I interaction is favored, which could be rationalized by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…3b). This is remarkably linear and directional compared to that of 1·(o-DITFB) 2 , which shows that a linear symmetric halogen bond Table 1 Crystallographic data and structure refinement parameters of co-crystals 1·(o-DITFB) 2 , 1·(m-DITFB) 2 ·DMSO, and 1·p-DITFB donor easily favours the formation of linear long chain assemblies propagated by C-I⋯O halogen bonds. Co-crystallization of 1 with m-DITFB consistently formed a three component crystal with a 1 : 2 : 1 ratio of 1 : m-DITFB : DMSO, regardless of the initial stoichiometry.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…3b). This is remarkably linear and directional compared to that of 1·(o-DITFB) 2 , which shows that a linear symmetric halogen bond Table 1 Crystallographic data and structure refinement parameters of co-crystals 1·(o-DITFB) 2 , 1·(m-DITFB) 2 ·DMSO, and 1·p-DITFB donor easily favours the formation of linear long chain assemblies propagated by C-I⋯O halogen bonds. Co-crystallization of 1 with m-DITFB consistently formed a three component crystal with a 1 : 2 : 1 ratio of 1 : m-DITFB : DMSO, regardless of the initial stoichiometry.…”
Section: Resultsmentioning
confidence: 94%
“…The most symmetrical XB donor p-DITFB gave rise to a 1 : 1 donor-acceptor co-crystal utilizing the CO⋯I synthon. On the other hand, o-DITFB and m-DITFB isomers resulted in 1 : 2 donor-acceptor co-crystals {1·(o-DITFB) 2 and 1·(m-DITFB) 2 ·DMSO} where both CO⋯I and type I/II iodine-iodine interactions were observed. DMSO in the structure of 1·(m-DITFB) 2 ·DMSO acted as a second XB acceptor molecule.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In a recent study, Hidalgo et al reported a series of five crystal structures of 1:1 halogen-bonded complexes between TFTIB and 4-[5-(4-alkoxyphenyl)-1,3,4-oxadiazole-2-yl]pyridine. In each of the five crystal structures, one TFTIB molecule formed three C−I• • • N halogen bonds with neutral halogen atom acceptors [26]. Unfortunately, the latter two studies did not discuss the factors controlling the formation of multiple halogen bonds with a single TFTIB molecule.…”
Section: Introductionmentioning
confidence: 98%